Strengths of the Social Safety Net in the Great Recession : Supplemental Nutrition Assistance and Unemployment Insurance - Wiseman, Michael (Michael L.); Wandner, Stephen A.; Stevens, David Wlater; O'Leary, Christopher J. (Book collections on Project MUSE., 2019)
The impacts of the Great Recession greatly tested the nation's social safety net. During this monumental economic downturn, the number of Unemployment Insurance (UI) recipients doubled from 10 million to 20 million, and the number receiving benefits through the Supplemental Nutrition Assistance Program (SNAP) ballooned from 20 million to 50 million. Many who lost their jobs became eligible for UI and often SNAP, too. Many already receiving SNAP lost jobs and became eligible for UI. While both programs were stressed, they proved to be flexible enough to respond to the needs of many of the victims of the recession. But little has been known about how the two programs interacted and how policies governing them may be altered to better respond to hardship when future downturns occur. This book shows that each program has considerable effects on the other and that policies governing them could be altered to better serve recipients of both programs. O Leary, Stevens, Wandner, and Wiseman present a group of papers using administrative data from six states compiled before, during, and after the Great Recession that show how the programs interact while highlighting factors that affect benefit eligibility and levels. Besides the state-specific chapters, the editors also present chapters that detail the background of the UI and SNAP programs and present a review of previous research on SNAP and UI interactions.